Double Encryption, Decryption Process Using Graph Labeling Through Enhanced Vigenere Cipher - Jaya Shruthy, V. N; Maheswari, V. (Journal of physics. Conference series, 2019)
In this paper, we promote Double encryption process of our secret text initially through Difference Labeling of Signed Graphs and then through the Vigenere Cipher technique. Thus we propose Double encryption and their corresponding decryption process thereby making prediction of secret text complicated.